The way of the modern warrior living the samurai ideal in the 21st century - Kaufman, Stephen 1939- Hanshi (North Clarendon, VT Tuttle Publishing, 2012)
The modern warrior applies his or her total energy and creativity in support of a just cause to resolve conflicts and promote the greater good. Their mission demands emotional wellbeing and intellect as well as strength. This book presents the ancient samurai warrior ethos developed and practiced in Japan for over 1000 years-the greatest expression of the warrior's code which the world has ever seen-as it applies to today's modern warrior. It is an essential handbook for those who are willing to live and die by the warrior's side
The samurai ideal and the new samurai -- Do not be afraid of change; it is the only thing that's dependable -- Think well of yourself and let that be your answer -- No one is responsible for your fallacies-probably not even yourself -- It is better to take the easy way in rather than the easy way out -- Accept pure harmony in your mind and body; it it isn't there, demand it of yourself -- If advice cannot be changed it isn't based on reality, except for what you tell others -- Things too easy to get are generally hard to keep -- A person who truly sees the difference in things sees sameness in all things -- Focus on principles, not politics -- Too many books cause confusion-except for the ones that you write --The goods men derive from conquest drives them mad for more -- The universe knows what it wants you to be and do-and so do you, which is why you reject it -- Accept the target's acceptance -- Take it -- Clever people have little self-esteem and so they always look to get over on someone -- Money is not the root of all evil but the meaningless things it buys are evil -- Ease and grace. Do it all with ease and grace, even that with ease and grace -- Do not seek to command; seek to teach. Do not seek to obey; seek to understand --Time stands still if you go fast enough -- Royalty suggests arrogance until overthrown by humility; then it becomes arrogance again -- Water penetrates the hardest stone as all gives way to persistence -- In power and quickness is strength and speed -- In times of strife wise men may use evil with more alacrity than you ever could -- deeds are more important than words, but not to poets --Appreciate yourself or you won't be appreciated -- People with nothing to say always have something to say -- Never choose cheap goods-they are much too costly -- The heart is essential if the intellect is to understand the spirit -- It is easier to understand the difficult than the simple -- Humble opinions are based on not knowing what you are talking about -- To perish quickly think only of yourself -- Education should never be confused with learning -- Be good to yourself first and then worry about the rest of the world -- If you can't do it right, you can't do it wrong -- If you're gonna play, paly-don't play -- Politeness is not a sign of weakness -- Humility is sometimes a very necessary thing-especially if you're outnumbered -- Understand the similarities of fate and free will -- There is no such thing as Yin and Yang, which is not to suggest that Yin and Yang do not exist -- Deceptive technique should be avoided whenever possible -- Hoping is based on non-acceptance; wishful thinking is willful denial -- You only know love if you know hate. It is best to know neither, but simply to be -- Do what you tell yourself to do and don't take no for an answer -- People will believe in anything that works, even when it doesn't -- Don't consider the rewards of your work and the results will be better -- To be one thing, you must also be the opposite -- Greatness spreads with wealth without restriction except to you, right? -- Heaven is obedient to all things. If that isn't true then you aren't here -- Be sure you're right and then proceed, even if you're wrong -- Give life and death to all things but don't seek to own them -- Endeavor to come to terms with the tragedy of your own inconsequence -- When you see a man in all of his glory know that he has known, or will know shame -- Say "thank you" even when you mean it -- Conquering your fears is the only victory worth having-so is conquering your joys -- Good fortune can be quelled by bad behavior even though bad behavior is sometimes virtuous
Keywords: Samurai; Martial arts -- Philosophy